Studi tingkat kesejahteraan masyarakat nelayan di Kampung Gurimbang Kecamatan Sambaliung Kabupaten Berau: Study on welfare level of fishing community at Gurimbang Village, Sambaliung Subdistrict of Berau - Eko Sugiharto; Salmani; Bambang Indratno Gunawan; Eko Sugiharto (Fakultas Perikanan dan Ilmu Kelautan, Universitas Mulawarman, 2022)
The purpose of this study was to determine the level of prosperity and the typology of rural fishing communities Gurimbang Village. By using several methods, namely the welfare of family planning by the national coordinating body (BKKBN) and village typology analysis based on three criteria: self-help, self-employment and self-sufficiency. The results of this study indicate that as many as 31 respondents (94%) of fishermen in Kampung disadvantaged families in the early stages and as many as 2 respondents (6%) are in phase I Family Welfare, and the typology of fishing communities included in the category of village Kampung Gurimbang Swakarya.